Structural data and immunomodulatory properties of a water-soluble heteroglycan extracted from the mycelium of an Italian isolate of Ganoderma lucidum. Issue 18 (17th September 2017) - Carrieri, Raffaele; Manco, Rosanna; Sapio, Daniela; Iannaccone, Marco; Fulgione, Andrea; Papaianni, Marina; de Falco, Bruna; Grauso, Laura; Tarantino, Paola; Ianniello, Flora; Lanzotti, Virginia; Lahoz, Ernesto; et al.
Abstract: Mushrooms produce a wide range of bioactive polysaccharides, different from each other in chemical structure and biological effects. In the last years, the idea to develop functional foods or drugs containing fungal polysaccharides is attracting great attention. Fruiting bodies of Basidiomycetes Ganoderma lucidum are commonly used in Oriental medicine to treat several disorders. G. lucidum polysaccharides – mainly β-glucans and heteroglycans – have numerous biological properties such as antitumour and immunomodulatory activities. This report shows, by gene expression analyses and bioenergetic assays, immunomodulatory properties and capacity to improve glucose metabolism of a water-soluble heteroglycan extracted from mycelium of an Italian isolate of G. lucidum . The findings suggest the use of the heteroglycan as probiotic or ingredient in functional foods, being easy to produce and disperse in a food matrix thanks to its water-solubility. Heteroglycan could exert protective effects in pro-inflammatory conditions and benefits for people characterised by suppressed immune response. Abstract :